(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Simulation-based education is transforming medical training by providing a safe and controlled environment for skill development, clinical decision-making, and team collaboration. This article explores the future of simulation in medicine, focusing on its potential to reduce medical errors, improve patient safety, and enhance clinical outcomes. Advances in artificial intelligence (AI), virtual reality (VR), and data-driven analytics are leading to more personalized learning experiences, allowing healthcare professionals to train more effectively. Additionally, remote and cloud-based simulations are increasing accessibility and flexibility in medical education. As technology continues to evolve, simulation will play a critical role in shaping a highly skilled and competent healthcare workforce, ultimately improving patient care and outcomes.